2015
DOI: 10.1080/00207160.2014.1000882
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to detect epistasis utilizing parallel implementation of ant colony optimization by MapReduce framework

Abstract: Genome-wide association studies (GWAS) involve the detection and interpretation of epistasis, which is responsible for the 'missing heritability' and influences common complex disease susceptibility. Many epistasis detection algorithms cannot be directly applied into GWAS as many combinations of genetic components are present in only a small amount of samples or even none at all. For a huge number of single nucleotide polymorphisms and inappropriate statistical tests, epistasis detection remains a computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Previous study showed that GWAS involve the detection and interpretation of epistasis. However, many epistasis detection algorithms cannot be directly applied into GWAS as many combinations of genetic components are present in only a small amount of samples or even none at all (Zhou et al, 2016). Linear mixed models (LMMs) are widely used in GWAS to account for population structure and relatedness, for both continuous and binary traits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that GWAS involve the detection and interpretation of epistasis. However, many epistasis detection algorithms cannot be directly applied into GWAS as many combinations of genetic components are present in only a small amount of samples or even none at all (Zhou et al, 2016). Linear mixed models (LMMs) are widely used in GWAS to account for population structure and relatedness, for both continuous and binary traits.…”
Section: Discussionmentioning
confidence: 99%
“…These two probability functions and the random selection mechanism increases the diversity of the search, and also has been adopted by other ACO methods, including epiACO(Z) [24], MACOED [25], [26], IACO [27], and epiACO(S) [28]. Zhou et al [29] developed a modified ACO method for detecting epistatic interactions, and implemented it on a hadoop cluster utilizing Google's MapReduce framework. Similarly, they provided another probability function to greedily find the best SNP, which was defined as…”
Section: A Path Selection Strategies 1) Probability Functionsmentioning
confidence: 99%
“…Though requiring more computational costs, the TuRF improves its performance when the data contain a large number of noise SNPs by iterating the ReliefF and deleting SNPs with the lowest ReliefF scores at each iteration. For the method proposed by Zhou et al [29], its heuristic information, they called it distance, was got by the following formula,…”
Section: ) Heuristic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Face with the current situation of domestic traffic, in order to find a reasonable driving route, is undoubtedly need processing for a huge data transportation. Currently, Developed by the Apache Software Foundation and the open source Hadoop distributed system architecture is very powerful platform for dealing with big date, its main core is a distributed file system (HDFS) to achieve big data storage and computing a MapReduce model [1,8] for parallel computing of massive data.…”
Section: Introductionmentioning
confidence: 99%